Answer
x/3 = 3
Explanation
Substituting x = 1 into the second equation:
![\begin{gathered} (x)/(1)=1 \\ (1)/(1)=1 \\ \text{ Simplifying} \\ 1=1 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/e57cr77innhrlj4hfltalvl8mydr6su4bc.png)
Given that the same result is obtained at both sides of the equation, then x = 1 is a solution to the equation.
Substituting x = 1 into the third equation:
![\begin{gathered} (x)/(4)=(1)/(4) \\ (1)/(4)=(1)/(4) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/ifc2zvfk2hr24ldffba7pfaeq6jhaq0hia.png)
Given that the same result is obtained at both sides of the equation, then x = 1 is a solution to the equation.
Substituting x = 1 into the fourth equation:
![\begin{gathered} (x)/(2)=(2)/(4) \\ (1)/(2)=(2)/(4)\text{ } \\ \text{ Simplifying} \\ (1)/(2)=(1)/(2) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/960z02azb8032o5rr8r9jephk4xjjjoq6v.png)
Given that the same result is obtained at both sides of the equation, then x = 1 is a solution to the equation.
Substituting x = 1 into the first equation:
![\begin{gathered} (x)/(3)=3 \\ (1)/(3)\\e3 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/symv4zsrwvfyh7sw2ed631jjc1f50la5wt.png)
Given that different results are obtained at both sides of the equation, then x = 1 is not a solution to the equation.